Peningkatan Kemampuan Memahami Bacaan Melalui Pembelajaran Kooperatif Tipe Stad Pada Siswa Kelas X SMA Negeri 1 Sintang - Trinadiah Trinadiah (LPD IKIP PGRI Pontianak, 2022)
Many of tenth grade students have difficulty in reading comprehension. This can be seen from the results of the test in the form of essays related to reading text comprehension where only 36% students scored above the minimum criteria. Another problem is that most students feel embarrassed or afraid to ask the teacher when they have learning difficulties. They more often ask their friends. Therefore, the writer raises the problem in this research whether the STAD (Student Team Achievement Divisions) type of cooperative learning model can improve students’ reading comprehension skills. The results showed that the learning model was effectively used in reading comprehension. This was evidenced by the increase in student activity in the learning process and test scores for learning outcomes after the implementation of this learning model. In the first cycle, student who achieve the minimum criteria were 58% with an average score of 70.19, the second cycle increased to 89% with an average score of 86.64, and in the third cycle all students had completed their studies with an average value is 92.39.